2011
DOI: 10.2214/ajr.11.6529
|View full text |Cite
|
Sign up to set email alerts
|

Real-Time Sonoelastography of Major Salivary Gland Tumors

Abstract: Although this study revealed a difference in elastographic score between benign and malignant tumors, detailed analysis did not provide consistent results. Consequently, real-time sonoelastography appears to be a limited technique in the differential diagnosis between benign and malignant salivary masses.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
50
1
3

Year Published

2012
2012
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(59 citation statements)
references
References 27 publications
(35 reference statements)
5
50
1
3
Order By: Relevance
“…6 One radiologist who was blinded to the pathologic findings or final diagnoses reviewed the static images, except for those of the 23 patients who were previously diagnosed as AML with CT. The strain ratio was measured by comparing the tumour (B) to the renal cortex for all renal lesions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…6 One radiologist who was blinded to the pathologic findings or final diagnoses reviewed the static images, except for those of the 23 patients who were previously diagnosed as AML with CT. The strain ratio was measured by comparing the tumour (B) to the renal cortex for all renal lesions.…”
Section: Discussionmentioning
confidence: 99%
“…Elastography in terms of the application of pressure to the probe has a relatively greater operator dependency, and strain values may change with different degrees of manual compression, as well as with the composition and structure of tissues. 19,20 Furthermore, various factors, such as lesion size, depth, and density can affect the performance of elastography, and it can be difficult to achieve optimal image quality for every case.…”
Section: -12mentioning
confidence: 99%
“…Because many diseases correlate with changes in the mechanical properties of tissues, this technique has been successfully applied in detecting and assessing various pathologies of thyroid gland, breast, lymph nodes, major salivary gland, prostate, kidney, and liver [1][2][3][11][12][13][14][15][16][17]. However, to our knowledge, no study has been reported previously in the medical literature using real time sonoelastography to assess gallbladder polyps.…”
Section: Discussionmentioning
confidence: 99%
“…Second, most of the gallbladder polyps were accepted as benign by sonographic follow-up without histopathological diagnosis. Third, elastography itself has certain limitations, including relatively high operator dependency, factors affecting the performance of elastography, such as size, depth, and density of the lesion, strain values containing variables with different degrees of compression and solid components affected by the lack of strain of the fluid portion [2,3,14,22]. Finally, description of the elasticity pattern is a subjective method.…”
Section: Discussionmentioning
confidence: 99%
“…1-3 However, elasticity imaging (both by qualitative and quantitative elastographic methods) is not definitive in distinguishing benign from malignant lesions in the salivary glands. [4][5][6][7][8][9] In particular, the appearance of pleomorphic adenomas Deniz Cebi Olgun, MD, Fatih Kantarci, MD, Umit Taskin, MD, Fahrettin Kilic, MD, Mehmet Faruk Oktay, Serdar Altinay, MD, Nuray Kepil, MD, Ibrahim Adaletli, MD, Mehmet Ada, MD, Ismail Mihmanli, MD Received July 2, 2013, Objectives-The purpose of this study was to evaluate whether the relative proportions of stromal to cellular components of pleomorphic adenomas have an effect on the shear elastic modulus determined by shear wave elastography (SWE).Methods-This study was approved by the Ethics Committee of our institution and performed between September 2011 and December 2012. Thirty-five patients who underwent surgery for a parotid mass were included in the study.…”
mentioning
confidence: 99%